Malang Meatballs as a Representation of Cultural Identity and Local Culinary Tourism: A Gastronomic Perspective - Fatimah Karim; Marwanti Marwanti (Jurnal Kawistara, 2026)
Local culinarians have been mostly studied in terms of economic and tourism aspects. Beyond this material dimension, this study examines Malang meatballs, popularly called Bakso Malang, as cultural identity as a representation that serves as both a symbol of regional identity and a pillar of the creative economy. Using the lens of gastronomy, the focus of this study is to trace the historical narratives, culinary practices, and symbolic values embedded in the product. Data was collected through observation, in-depth interviews, and documentation at four iconic businesses, including the grilled meatballs of Pak Man, meatballs of Damas, meatballs of Bejo, and meatballs of Priyangan. Analysis was conducted thematically with verification through triangulation of sources. The findings indicate that Malang meatballs represent a cultural identity that reflects the creativity and resilience of the local community. Sustained innovation in processing techniques and presentation styles, as seen in the businesses studied, has proven to enrich consumers’ sensory experiences without eroding their traditional roots. Strategic business locations and inclusive service offerings also contribute significantly to Malang’s culinary tourism landscape, as evidenced by the achievement of 3.1 million tourist visits in 2024